Faktor-Faktor yang Mempengaruhi Pembelian Jasa Internet di Kota Semarang - Lutvi Hastowo (Jurnal Ilmiah Aset, 2009)
Tight business competition, make cyber café service manager must analyze how to keep its customer. Price, service, location and facilty are predicated variables that influence toward decision making for using internet at cyber café service. The objective of this research was to analyse the influence of price, service, location and facility toward decision of using internet at cyber café service Lintas Net 2 in Semarang city. Result of this research indicate that price, service, location and facility able to explain influence decisionof using internet at cyber service Lintas Net 2. The dominant variable that influence on the decision of using internet at cyber café service Lintas Net2 in Semarang city in this research is service.